The Effect Of Trust, Employee Engagement On Employee Performance Mediation By Job Satisfaction In Private Banking Companies In Indonesia - Wibisono, Wibisono; Wahyu Gunawan P, Andreas (Journal of Comprehensive Science, 2023)
This study aims to examine and analyze the "Effect of Trust. Employee Engagement, on employee performance through job satisfaction in private banking companies in Indonesia consisting of 150 respondents. Weak respondents based on Gender, Age, Education. The test results show that Trust has a positive effect on Employee Performance Employee Engagement has a positive effect on Employee Performance Trust has a positive effect on job satisfaction, employee involvement has a positive effect on job satisfaction, job satisfaction has a positive effect on employee performance, trust has an effect on employee performance through job satisfaction, employee involvement has an effect on employee performance through job satisfaction.